Regional clinical and economic model of colorectal cancer screening - P. V. Nesterov; A. V. Ukharskiy; N. V. Kislov (Исследования и практика в медицине, 2020)
Purpose of the study. To evaluate the clinical and economic efficiency of colorectal cancer screening model in the Yaroslavl region. Materials and methods. To achieve this goal, we have given a clinical and economic assessment of the existing approach to the diagnosis and treatment of colon cancer. We have also developed a clinical and economic model of colorectal cancer screening strategy in the Yaroslavl region. After that, we made a comparative assessment between the strategies on such parameters as total costs, efficiency, and CER coefficient. Results. The strategy for the absence of colorectal cancer screening has a cost-effectiveness rate equal to 246 712 rubles (3820$)/LYG, with the value of added years of life in 2.9 years. According to our calculations, the implementation of the program of screening of CRC based on fecal occult blood immunochemical method, followed by the implementation of colonoscopy in the case of a positive result, will require an increase in funding for patients with colon cancer by 6.9% per year. At the same time, by changing the structure of morbidity and increasing the part of early forms in the implementation of the screening program, an increase in the estimated life expectancy of patients will be achieved, which is consistent with the long-term results of programs conducted in Europe and the United States. The CER for the screening strategy is 103.95 thousand rubles (2030$) / LYG. Long-term modeling shows that the introduction of screening program will reduce the incidence of CRC by 12% from the baseline by the 15th year of implementation and reduce the cost of diagnosis and treatment of colon cancer by 16.1% per year without taking into account inflation expectations. Conclusion. The introduction of a colorectal cancer-screening program at the regional level is clinically effective and cost-effective.